Race, Prostitution and the New Left: the Postwar Inner City through Janet Mendelsohn's 'Social Eye'. Issue 1 (7th June 2017) - Connell, Kieran
Abstract: This article examines the changing dynamics of a postwar British inner-city through the photographic lens of Janet Mendelsohn, an American student at the Birmingham Centre for Contemporary Cultural Studies. Between 1967 and 1969 Mendelsohn took more than 3, 000 photographs and conducted scores of interviews with her subjects, although hitherto her work has remained largely unknown. Through her focus on Balsall Heath, one of the country's largest 'red light' districts, Mendelsohn's work offers a window onto the significant changes taking place there, which included the arrival and settlement of immigrants from the Caribbean and South Asia, the advancement of slum clearance and growing anxieties about prostitution. Through the distinctiveness of her 'social eye' and emphasis on the life of a single sex-worker in Balsall Heath this article shows how Mendelsohn was able to foreground the ambiguous, contradictory nature of the social practices that took place there.